Combining strategy of genetic algorithm and particle swarm algorithm for optimum problem of RFID reader. (24th March 2015) - Lu, Jin-gui; Li, Hong-liang; Chen, Feng-xin; Chen, Lei
This paper is involved in optimisation problem of location and number of reader for RFID recognition system. The combining strategy of genetic algorithm and particle swarm algorithm is given for optimisation problem of RFID reader in this paper. The combining strategy includes two optimisation stages, and the optimisation number of reader for RFID will be obtained by genetic algorithm in the first stage, and the optimisation location of reader will be obtained by particle swarm algorithm in the second stage. The computer implementation on the combining strategy is made for optimisation of number and location of RFID reader. The numerical example is given for the combining strategy for optimisation problem of RFID reader.